Methodological Competence of Philology Students in Higher Education: the Linguodidactic Potential of Innovative Teaching Technologies (Eurasian Journal of Philology Science and Education, 2026)
This article examines the issue of developing methodological competence among philology students within the higher education system. The relevance of this study stems from the contradiction between the growing demands for the professional readiness of language teachers and the insufficient development of the theoretical foundations for integrating innovative technologies into methodological training. The study is theoretical and analytical in nature and draws on competency-based, activity-based, and language-didactic approaches. The paper systematizes existing concepts of the structure of methodological competence developed within the global pedagogical tradition and proposes an original six-component model comprising cognitive-linguistic, methodological, design-technological, communicative-pedagogical, reflective-research, and axiological components. The didactic potential of key innovative technologies is described: blended learning, project-based learning, the corpus-based approach, gamification, and digital educational platforms. Particular attention is paid to the Kazakhstani context: the specifics of the multilingual educational environment are examined, and the experience of the country’s leading teacher-training universities is analyzed. Systemic problems in the implementation of innovative technologies in teacher training are identified, and promising directions for its improvement are defined. The conclusion is drawn regarding the need for the purposeful design of a university’s methodological framework, taking into account the requirements of modern language education and the national educational priorities of the Republic of Kazakhstan. The study also reveals that the Kazakhstani multilingual educational context imposes specific demands on the methodological training of philology students, particularly in relation to trilingual education policy. The findings contribute to the theoretical understanding of how university-level methodological preparation can be restructured to meet contemporary challenges in language pedagogy. The results of this study may serve as a basis for developing curricula, methodological modules, and professional development programs for language teacher educators in Kazakhstan and beyond.Keywords: methodological competence, philology students, linguodidactics, innovative technologies, higher education, language education, Kazakhstan.